Contextual Approach Analysis In Improving Civics Learning Outcomes In Elementary Schools - Br. Ginting, Susanna; Simanullang, Reno Francius; Yunita, Sri; Dharma, Surya (Jurnal Ilmu Sosial Mamangan, 2025)
The purpose of this study was to examine students' civics learning outcomes using contextual methods. From the results of the study, it can be concluded that the contextual learning approach is suitable for use in civics learning in schools. By relying on previously existing ideas and understandings to be interpreted based on works that trigger discussion, the author of this study used descriptive-critical research with a greater focus on the strength of the analysis of existing sources and data. The results of the study showed that students were more confident, teachers were more responsive to students' needs, and student learning outcomes in class increased. The increasing seriousness and enthusiasm of students, the decreasing gap in knowledge between them, their increasing desire to learn outside of school, the emergence of innovative ideas from students and teachers to improve the quality of education in their respective schools, and the growing sense of unity and synergy between students and teachers are contributing factors. As a result, students actively participate in the learning process, so that learning becomes more meaningful. The results of observations during civics learning showed that students began to actively ask questions to build their understanding of Pancasila values. Students were able to share thoughts about other students' experiences of Pancasila values during group learning activities. Thus, it can be said that students' PPKn learning outcomes can be improved by using contextual learning strategies